Assessing the Kinematic GPS Positioning Performance Under the Effect of Strong Ionospheric Disturbance Over China and Adjacent Areas During the Magnetic Storm. Issue 2 (29th January 2022) - Geng, Wei; Huang, Wengeng; Liu, Guoqi; Liu, Siqing; Luo, Binxian
Abstract: The geomagnetic storm caused numerous disturbances of the ionosphere, particularly, plasma irregularities, which can affect the accuracy of Global Positioning System (GPS) positioning. This study quantifies the impacts of the ionospheric disturbance on GPS precise point positioning (PPP) solutions during extreme space weather events by taking advantage of 260 GPS stations in China. The results show that the average positioning error in China increased significantly during the ionospheric disturbance on 08 Sep 2017. By comparing the kinematic GPS‐PPP (3‐D) error distribution map and the ROTI index map, it is found that the ionospheric irregularities are one of the main reasons for degrading the GPS positioning accuracy. The statistical analysis results show that when the ionospheric scintillation index S4 is greater than 0.4, the average kinematic GPS‐PPP error calculated by the station is higher than 0.8 m. Plain Language Summary: Global Positioning System (GPS) precise positioning performance will be strongly affected under severe ionospheric anomaly conditions. This paper analyzes the effects of ionospheric disturbances caused by geomagnetic storms on 260 GPS stations in China. The results show that kinematic precise point positioning (PPP) solutions degraded following an intensified auroral particle precipitation during the storm's main phase when up to ∼70% of the low‐latitude stations experienced degraded position solutions in the multimeter. Subsequently, the comparison of the kinematic GPS‐PPP (3‐D) error distribution map and the ROTI index map has shown that the ionospheric irregularities are one of the main reasons for degrading the GPS positioning accuracy. Finally, select the time period during which ionospheric disturbance events occur continuously, and systematically discuss the impact of ionospheric scintillation on GPS‐PPP positioning accuracy. The statistical analysis results show that when the ionospheric amplitude scintillation index S4 is greater than 0.4, the average kinematic GPS‐PPP error calculated by the station is higher than 0.8 m. Key Points: Ionospheric disturbances caused Global Positioning System (GPS) positioning degradation during a magnetic storm on 08 September 2017 over China and adjacent areas Ionospheric irregularities caused by magnetic storm is one of the important reasons that affect the accuracy of GPS positioning Ionospheric disturbances affect the occurrence of GPS cycle slips, thereby affecting GPS positioning performance and accuracy